Public Perception of Health Insurance Technology-Based Innovation in Indonesia - Irawan, Bambang; Putri, Tasya Kamila; Zulkifli, Zarina; Akbar, Paisal (Jurnal Administrasi Publik (Public Administration Journal), 2023)
This study aims to obtain an overview and analyze public perceptions in implementing technology-based health insurance service innovations in the Mobile National Health Insurance (JKN) application conducted by the Indonesian Health Social Security Administration Agency (BPJS). This study used descriptive qualitative method. This research data is generated from the comments column of the JKN mobile application in the AppStore and Play Store. Data collection is done by data mining and data extraction. The data analysis used in this research is Qualitative Data Analytics (QDA). The analytical tool used in this study is Qualitative Data Software Analysis (QDSA) Nvivo 12 Plus. The results of the study show several things, namely the first is related to the features available in the Mobile JKN application. The second is related to the number of downloaders and the number of active users of the Mobile JKN application, and the third is related to the perception generated by users while using the Mobile JKN application. Where it was found that overall public perception of the application of technology-based health insurance service innovations through the JKN mobile application by the Indonesian BPJS Health obtained a perception that tended to be negative. This is shown by the five indicators that mostly get a bad perception from the public, and only two indicators that fully capture good or positive perceptions. Apart from that, other findings also show the dominant sentiment generated while this application is used by the public in obtaining health services.